2020
DOI: 10.3233/hab-200407
|View full text |Cite
|
Sign up to set email alerts
|

MTT assay dataset of polyethylenimine coated graphenoxide nanosheets on breast cancer cell lines (MCF7, MDA-MB-231, MDA-MB-468)

Abstract: Graphen oxide has emerged as a promising tool in medical biotechnology due to its outstanding properties applicable in several fields as well as cell imaging, drug and gene delivery. Monolayer structure and high surface area of Graphen benefits elevated loading capacity of drugs rather than other nanomaterials. However Graphen oxide in physiological solutions has unfavourable reactions which confine it’s application in biomedical field without additional surface functionalization. Coating of graphenoxide by po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…MTT is one of the most widely used investigation method of in vitro cell viability, proliferation, cytotoxicity, and chemical and radiation sensitivity studies (10)(11)(12)(13)(14)(15). The idea of visualizing MTT reduction on a cellular basis originated from the purpose of enlightening researchers on how to use visual analysis methods in extraordinary situations that they may encounter.…”
Section: Discussionmentioning
confidence: 99%
“…MTT is one of the most widely used investigation method of in vitro cell viability, proliferation, cytotoxicity, and chemical and radiation sensitivity studies (10)(11)(12)(13)(14)(15). The idea of visualizing MTT reduction on a cellular basis originated from the purpose of enlightening researchers on how to use visual analysis methods in extraordinary situations that they may encounter.…”
Section: Discussionmentioning
confidence: 99%
“…After removing the supernatant, dimethyl sulfoxide (DMSO) was added to stop formazan formation. The 96-well plate was then shaken for 15 min in the dark at RT, and absorbance was measured at 570 nm ( Maleki et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Polymer materials, such as polyethylene glycol (PEG) [ 86 ], polyethyleneimine (PEI) [ 92 ], polyvinyl alcohol (PVA) [ 93 ], dextran (DEX) [ 90 ], polyacrylic acid (PAA) [ 94 ], and chitosan [ 95 ], have been covalently bonded to enhance the biocompatibility and stability of GO-based delivery systems. Covalent modification routes are generally carried out using three different reactions: (1) a ring-opening reaction of epoxide groups present on the basal plane of GO via nucleophilic attacks; (2) amidation, where COOH groups at the edges of GO flakes are replaced by NH 2 in polymer groups; (3) esterification, in which carboxylic groups of GO directly react with hydroxyl groups of the polymer in the absence of NH 2 as a mediator agent [ 17 , 77 , 91 ], as illustrated in Figure 2 .…”
Section: Characteristics Of Go As a Nanocarriermentioning
confidence: 99%
“…Furthermore, aggregates of GO carriers could have large dimensions, making them unable to cross biological barriers and accumulate inside cells and tissues, increasing the toxic effect [ 57 ]. Thus, GO in physiological solutions induces unfavorable reactions for putative applications in the biomedical field, limiting its use without further surface modifications [ 92 ]. As previously said in Section 2 , studies have demonstrated that the use of polymers, such as PEG [ 86 ], PEI [ 92 ], PVA [ 93 ], DEX [ 90 ], PAA [ 94 ], and chitosan [ 95 ], which were covalently bonded to GO functional groups, can enhance the biocompatibility and stability of GO-based drug or gene delivery systems.…”
Section: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation